Evaluation of the impacts of reiki touch therapy on patients diagnosed with fibromyalgia who are followed in the pain clinic - ALPAR, ŞULE (My University, 2023)
The aim of this study is to investigate the effects of Reiki application on pain, anxiety, and quality of life in patients with fibromyalgia. The study was completed with a total of 50 patients: 25 in the experimental group and 25 in the control group. Reiki was applied to the experimental group and sham Reiki to the control group once a week for 4 weeks. Data were collected from the participants using the Information Form, Visual Analog Scale, McGill-Melzack Pain Questionnaire, State-Trait Anxiety Inventory, and Short Form-36. There was a significant difference between the mean Visual Analog Scale pain scores during and before the first week (P = .012), second week (P = .002), and fourth week (P = .020) measurements of the individuals in the experimental and control groups, after application. In addition, at the end of the 4-week period, the State Anxiety Inventory (P = .005) and the Trait Anxiety Inventory (P = .003) were significantly decreased in the Reiki group compared with the control group. Physical function (P = .000), energy (P = .009), mental health (P = .018), and pain (P = .029) subdimension scores of quality of life in the Reiki group increased significantly compared with the control group. Reiki application to patients with fibromyalgia may have positive effects on reducing pain, improving quality of life, and reducing state and trait anxiety levels.
Keywords: Tıp; Hemşirelik; Sağlık Bilimleri; Medicine; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENTEGRE VE TAMAMLAYICI TIP; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; INTEGRATIVE & COMPLEMENTARY MEDICINE; NURSING; Tamamlayıcı ve Alternatif Tıp; İleri ve Uzman Hemşirelik; Complementary and Alternative Medicine; Advanced and Specialized Nursing; fibromyalgia; pain; Reiki; soft tissue rheumatism; therapeutic touch